Manufacturing Process of 46XX High-Capacity, High-Density Cylindrical-Type -Battery Cell Can - Hong Jong-Hwa; Seo Ye-Chan; Ji Sumin; Lee Sedong; Seong Hongseok; Yoon Eun-Yoo (MATEC Web of Conferences)
Among battery cells of various form factors, cylindrical-type battery cells are advantageous in mass production and relatively economical compared to other form factors. As the demand for higher storage capacity gradually increases, automobile manufacturers focus more on developing high-capacity and high-density batteries such as 46XX (where 46 means diameter and XX height ranging from 80 to 115). The energy capacity of the 46XX battery cells is over five times greater than that of the 1865 and 2170 cells. However, since no manufacturers were previously producing the 46XX, new issues were emerged in the process of manufacturing these new large-capacity cells. This research studies the manufacturing of the 46XX large-capacity cylindrical battery cell can through a multi-step forming process, utilizing finite element analysis. It also explores the industrial challenges encountered during the production of cylindrical battery cells and highlights the obstacles that need to be addressed for the widespread industrial application of the 46XX large-capacity cylindrical battery cell can.